(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The woman empowerment program and the subsequent development of New Woman has turned into a widespread event. The woman who is made mindful of her entitlement to be acknowledged as an individual and to be dealt with equivalent to man is restoring from the cinders of the traditional Indian woman as the New Woman of India, as another incarnation of Shakti. This new woman is exceptionally decisive, independent and solid willed and subsequently, again her predicament proceeds for the independent presence and personality in this male overwhelming society. Her present quandary is to dispose of the article of clothing of tradition and to get modernized. Man exploits this internal battle of woman and proceeds with his predominance over her though woman proceeds with her battle grabbing amongst tradition and innovation to pick up equity with man. All things considered, the rise of the new woman connotes the enlivening of woman into another acknowledgment of her place and position in family and society. In this we learned about the view purpose of female English scholars towards the idea of feminism.